Identity negotiation on the LIHKG platform: a grounded theory study of Mainland Chinese immigrants’ adaptation to Hong Kong society - Lingxiao Zhang; Tao Shen (Frontiers in Psychology)
In digital societies, social media has emerged as a critical arena for immigrant communities to engage in identity construction, yet there remains limited research on identity negotiation within specific digital platforms in the Chinese context. This study examines how Mainland Chinese immigrants negotiate identity, express emotions, and engage in social interactions on Hong Kong’s LIHKG platform (a locally dominant online forum established in 2016 that serves as Hong Kong’s primary community discussion platform) to adapt to the local socio-cultural environment. The research conceptualizes place as both physical location (Hong Kong as destination) and digital space (LIHKG as virtual locale), exploring how these intersecting spatial dimensions shape identity construction processes. Using grounded theory methodology, we analyzed 800 platform posts and conducted in-depth interviews with 20 Mainland Chinese immigrants. Results reveal a dynamic identity negotiation process characterized by four patterns (integrative, confrontational, collaborative, and avoidance) that immigrants strategically employ across different contexts. Place emerges as a fundamental organizing principle, with immigrants navigating between physical Hong Kong, digital platform spaces, and imagined cultural territories in their identity work. Emotions emerged as critical resources in identity construction, with specific regulation strategies developed to navigate exclusionary experiences. Interactions between immigrants and locals demonstrated significant topic differentiation, with political discussions exhibiting heightened boundaries while professional and everyday topics facilitated collaborative engagement. LIHKG’s platform features—including anonymity mechanisms and voting systems—fundamentally shape these identity expressions and group dynamics. This research contributes to migration studies by incorporating both digital and physical place dimensions into traditional frameworks, integrating emotional sociology, and developing localized theoretical models specific to Hong Kong-Mainland relations. The findings offer implications for digital inclusion policies, platform governance, immigrant support services, and construction of inclusive public discourse across multiple place-based contexts.